2014
DOI: 10.1039/c4cc07798a
|View full text |Cite
|
Sign up to set email alerts
|

Anion-tunable control of thermal Z→E isomerisation in basic azobenzene receptors

Abstract: Herein, we report that thermal Z→E isomerisation of simple azobenzene urea derivatives is selectively and predictably controlled by anion binding. The rate of this process depends strictly on the anion concentration and its binding affinity to the Z-isomer of the azobenzene host, i.e. increased rate constants are observed for higher anion concentration as well as for more strongly bound guests. The origin of this phenomenon is attributed to the electron density transfer from the anion to the host π-system, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 41 publications
3
51
0
1
Order By: Relevance
“…The electronic effects would seem to be the dominant factor for all guests except Succ = . The suggestion that electron density donation from the bound anions to the azobenzene unit of cis ‐ 2 could be responsible for the observed enhanced rate of cis / trans isomerizations is consistent with a recent study on the effects of anion binding in azobenzene derivatives containing urea units 30. Further studies are in progress in our laboratory, including molecular modeling and variable temperature experiments, to verify the way in which the different bis‐anions affect the isomerization kinetics of the azobenzene unit of receptor 2 .…”
Section: Methodssupporting
confidence: 89%
“…The electronic effects would seem to be the dominant factor for all guests except Succ = . The suggestion that electron density donation from the bound anions to the azobenzene unit of cis ‐ 2 could be responsible for the observed enhanced rate of cis / trans isomerizations is consistent with a recent study on the effects of anion binding in azobenzene derivatives containing urea units 30. Further studies are in progress in our laboratory, including molecular modeling and variable temperature experiments, to verify the way in which the different bis‐anions affect the isomerization kinetics of the azobenzene unit of receptor 2 .…”
Section: Methodssupporting
confidence: 89%
“…In 2014 the group of Jurczak reported the synthesis of receptor 15 (Figure ), featuring an azobenzene moiety bearing either one ( 15 a ) or two ( 15 b ) urea recognition sites in the para position . Building on the idea for which it would be desirable to trigger the switching using a different stimulus than light and heat, in this work, the scientists focused their studies on gaining kinetic control of the thermal Z → E isomerization through the use of chemical triggers.…”
Section: Configurational Selection Following Anion Complexationmentioning
confidence: 99%
“…The cis – trans isomerization reaction is one of the most studied reactions with regard to chemical control and chemical switching, for example by light8 or mechanical force 9. Very recently it has been shown that the cis – trans isomerization rate can be tuned by the presence of a nearby anion 10…”
mentioning
confidence: 99%